Kasagia sudhakari, a new species of deep-sea spider crab (Crustacea: Brachyura: Majidae) from the southeastern Arabian Sea. Issue 3 (16th March 2019) - Padate, Vinay P.; Manjebrayakath, Hashim; Ng, Peter K.L.
ABSTRACT: Kasagia sudhakari, a new species of spider crab, is described from two male specimens from southeastern Arabian Sea. This species differs from its only congener Kasagia arbastoi Richer de Forges & Ng, 2007, from the Philippines in the shape and form of the carapace, shape of the pseudorostral spines, arrangement of the orbital plates (supraorbital eave separated from the postorbital spine), size of the lateral branchial tubercles, as well as structures of the interantennular spine, hepatic lobe, cheliped, ambulatory merus and male first gonopod.